Association of Epicardial Adipose Tissue Thickness with Cardiovascular Risk in Acromegaly - Bulent CAN; Fatma OLCAY COSKUN; Sercin OZKOK; Mumtaz TAKIR (Medeniyet Medical Journal)
Objective: Acromegaly is a rare disease associated with increased mortality. Reports on coronary artery disease in acromegaly are controversial. This study aimed to investigate the possible association of epicardial adipose tissue thickness with cardiovascular risk in patients with acromegaly. Methods: The study included 38 patients followed up with the diagnosis of acromegaly and 29 healthy controls. Patients with acromegaly were divided into controlled and uncontrolled acromegaly groups based on insulin-like growth factor-1 levels. Epicardial adipose tissue thickness measurements were obtained from chest computed tomography, and laboratory data were extracted from patient files. Results: Twenty-nine patients (76.3%) had controlled acromegaly. Eleven patients with acromegaly had diabetes mellitus (28.9%), 18 (47.4%) had hypertension, and 27 (71%) had a concomitant chronic disease. Epicardial adipose tissue thickness was significantly increased in the acromegaly group (p<0.001). No significant difference was observed between the controlled and uncontrolled acromegaly groups in terms of the epicardial adipose tissue thickness. Age was the only parameter that was significantly correlated with the epicardial adipose tissue thickness. When the Framingham risk score was calculated, the 10-year cardiovascular risk of patients with acromegaly was 5.63%. Conclusions: The epicardial adipose tissue thickness is increased in acromegaly. However, this increase may not have clinical relevance in terms of cardiovascular risk.